Energy Analysis of Traditional Non-motorised Gill Net Operations, in Vembanad Lake, Kerala, India - R., Boopendranath M; M., Shahul Hameed (Fishery Technology, 2025)
Fish production and energy requirement in the traditional non-motorised gill netoperations, in Vembanadu Lake, Kerala, India are discussed in this paper. Gillnetting istargeted at mullets and other estuarine resources and is operated from traditional two-mencanoes of 5.5 m LOA, using paddling as means of propulsion. Fishing operations take placefrom November to July while during the other months it is suspended due to the presenceof large quantities of macro-vegetation, drifting downstream. Mean number of days ofoperation is 225 days. Mean catch per year per gill-netter was estimated to be 8.4 t of whichmullets contributed 25.1%, followed by sciaenids 17.1%, carangids 15.5%, cat fishes 13.6%, prawns 13.3% and miscellaneous fishes 15.2%. GER.t fish-1was found to be 0.61 GJ making this one of the most energy efficient system. Nearly 98.92% of the GER is contributed by fishing gear and the balance by the fishing canoe. Energy efficiency ratio was 8.01 and energy intensity value was 0.125.